Stimulasi Partisipasi Masyarakat dalam Perencanaan Pembangunan Kawasan melalui Optimalisasi Keahlian Pemetaan Menggunakan Drone - Zulkia, Dwi Rizka (Fakultas Teknik, Universitas Bangka Belitung, 2023)
KOTAKU Bangka Regency, is a program that focuses on addressing slum areas within Bangka Regency. Improving the quality of the residential environment is a mandate from the government outlined in the 2020-2040 RPJMN (National Medium-Term Development Plan). This involves enhancing the quality of slum areas, preventing the growth of new slum settlements, and promoting sustainable living. When planning an area, spatial data is crucial to support the planning process. Currently, the available spatial data is in the form of digital maps from Google Earth, but the quality is subpar, often appearing blurry and unreadable due to cloud cover. Spatial data can be processed through aerial photos taken using drones. However, Bangka Regency's